Das moderne Konzept der internen Subventionierung als Kriterium zur Identifizierung von Wettbewerbsverzerrungen bei europaïschen Agrarumweltmaßnahmen - Karin Holm-Mul̈ler; Heinz Peter Witzke (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2002)
– The "Rule of Additional Costs" and Modern Economic Theory - Applied to Payments for Ecological ServicesBoth WTO and the EU use a "Rule of additional costs" (RAC) to restrict payments for ecological services in agriculture in order to prevent trade distortions. We assess this rule in the light of modern economic theory. It is shown that the RAC is efficient, if conventional agriculture is competitive without other payments. In regions where agriculture is not competitive though and is said to be important for ecological purposes the payments for ecological services must exceed additional costs. In these cases three criteria exist to prevent trade distortions as far as possible: the regions in which farmers are eligible to more than additional costs must be clearly defined by economic and ecological indicators, payments must not exceed the costs for equivalent nature conservation measures by non-farmers and the ecological benefit of the farmer's actions must be demonstrated. The definition of the regions where more than additional costs can be paid should be made at the EU-level if the ecological importance of these regions is of international concern.
Keywords: 330; Landwirtschaft; Landschaftsschutz; EU-Agrarpolitik; Internalisierung externer Effekte; Internationaler Wettbewerb; EU-Staaten; EU-Umweltpolitik